AUDITOR PROFESSIONAL BEHAVIOR IN AUDIT (INTERNATIONAL SEMINAR, 2023)
This research uses a descriptive type of research with a quantitative approach which is measured using a multiple linear regression-based method. The population of this research is Public Accounting Firms in the Malang City area. The sample was determined based on the convenience sampling method, with a total of 60 respondents. Hypothesis testing using partial test (t test) and simultaneous test (f test). The results of multiple linear regression testing prove that the results of linear regression analysis are Y = 7.020 + 0.309X1 + 0.275X2 + 0.247X3 + 0.264X4 + 0.259X5states the regression of the Integrity variable (X1) with a value of 0.309, Objectivity (X2) with a value of 0.275, and Security (X3) with a value of 0.247has a positive effect on Audit Quality (Y), while the variable Capacity/Competency (X4) with a value of 0.264 and Professional Behavior (X5) with a value of 0.259 has no positive effect on Audit Quality(Y). The results of data analysis using a simultaneous test (f test), namely the variables Integrity (X1), Objectivity (X2), Security (X3), Capacity/Competency (X4) and Professional Behavior (X5) together have a significant effect on Audit Quality (Y).